PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT, INTELLECTUAL CAPITAL DAN ISLAMIC SOCIAL REPORTING TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Industri Dasar dan Kimia yang Masuk dalam Daftar Efek Syariah Periode 2016-2018) - Ghina Ziida Amalia; Warno Warno; Ari Kristin Prasetyoningrum (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
The purpose of the research was to determine the effect of enterprise risk management disclosure, intellectual capital disclosure and islamic social reporting on firm value.type of this research uses a quantitative method with multiple linear regression data alalysis techniques. The data used in this research is secondary data. Thepopulation of this research are basic and chemical industrial company in the List of Sharia Securities in the period 2016-2018. The sample used purposive sampling method, amounted to 48 samples. The resultof this research indicate that first, enterprise risk management does not effect on firm value. Second, intellectual capital positive and significant effect on firm value. Third, islamic social reporting does not effect on firm value.